Innovative maritime logistics in achieving higher flexibility and resilience : a two-stage QFD approach to improve maritime supply chain resilience - Cui, Can (2015)
Today, customer service quality has become increasingly important in supply chain management and maritime supply chain management. To deliver superior customer value, maritime supply chains need to have proper resilience measures to respond to maritime risks that could cause disruptions to supply chains. Although there are studies on risk assessment for maritime supply chains, there are few studies that examine the resilience measures to counter these risks. This paper aims to design a model to identify and prioritize resilience measures for shipping lines from a maritime supply chain perspective.